Increased phosphorylation of collapsin response mediator protein-2 at Thr514 correlates with β-amyloid burden and synaptic deficits in Lewy body dementias. Issue 1 (December 2016) - Xing, Huayang; Lim, Yun-An; Chong, Joyce; Lee, Jasinda; Aarsland, Dag; Ballard, Clive; Francis, Paul; Chen, Christopher; Lai, Mitchell
Abstract Collapsin response mediator protein-2 (CRMP2) regulates axonal growth cone extension, and increased CRMP2 phosphorylation may lead to axonal degeneration. Axonal and synaptic pathology is an important feature of Lewy body dementias (LBD), but the state of CRMP2 phosphorylation (pCRMP2) as well as its correlations with markers of neurodegeneration have not been studied in these dementias. Hence, we measured CRMP2 phosphorylation at Thr509, Thr514 and Ser522, as well as markers of β-amyloid (Aβ), tau-phosphorylation, α-synuclein and synaptic function in the postmortem neocortex of a longitudinally assessed cohort of LBD patients characterized by low (Parkinson's disease dementia, PDD) and high (dementia with Lewy bodies, DLB) burden of Alzheimer type pathology. We found specific increases of pCRMP2 at Thr514 in DLB, but not PDD. The increased CRMP2 phosphorylation correlated with fibrillogenic Aβ as well as with losses of markers for axon regeneration (β-III-tubulin) and synaptic integrity (synaptophysin) in LBD. In contrast, pCRMP2 alterations did not correlate with tau-phosphorylation or α-synuclein, and also appear unrelated to immunoreactivities of putative upstream kinases glycogen synthase kinase 3β and cyclin-dependent kinase 5, as well as to protein phosphatase 2A. In conclusion, increased pCRMP2 may underlie the axonal pathology of DLB, and may be a novel therapeutic target. However, antecedent signaling events as well as the nature of pCRMP2 association with Aβ and other neuropathologic markers require further study.